Origin of Antecrysts in Igneous Rocks from the Salavat Range (NW Iran): an Explanation for the Geochemical Signature of Potassic Alkaline Rocks. (6th April 2021) - Soltanmohammadi, Azam; Grégoire, Michel; Ceuleneer, Georges; Benoit, Mathieu; Bédard, L Paul; Gouy, Sophie; Rabinowicz, Michel
Abstract: Abundant silica-undersaturated potassic lavas are found in the centre of the Turkish–Iranian plateau (NW Iran) as flows, pillows and dykes. They display abundant zoned clinopyroxene macrocrysts and xenoliths of igneous cumulates. We determined four types of zoned crystals (Type-I, -II, -III and -IV) on the basis of their composition and zoning patterns. Use of in situ compositional data, together with whole-rock major and trace elements and the isotopic signatures of the host lavas provided evidence for the derivation of the different types of zoned clinopyroxenes from at least two contrasting parental melts. Our findings are consistent with an origin of the ultrapotassic and sodic alkaline melts from the deep-seated compaction pockets inferred from our previous studies of the alkaline magmatism throughout the Turkish–Iranian plateau. The ultrapotassic melt, which accumulated at the top of the compaction pockets, eventually ponded close to the spinel–garnet mantle transition and generated colourless antecrysts (Type-I and Type-II) and clinopyroxenite cumulates. When the compaction pocket impinged on the continental lithosphere, interstitial melts segregated and flowed inside dykes where grass green antecrysts (Type-III) and zoned phenocrysts (Type-IVa) crystallized from a melt having a geochemical signature of sodic alkaline melt. Later, at the crustal level, melt crystallization processes produced Type-IVb zoned phenocrysts. Our results are at odds with the paradigm of potassic magmas in NW Iran being derived strictly from a single mantle source.